Turbidity Measurement Using An Optical Tomography System - Sallehuddin Bin Ibrahim (Chemical Engineering Diponegoro University, 2013)
Turbidity is used to describe water quality and it can be caused by the presence of suspended particles and organic matter such as algae, clay and silt. The measurement of turbidity level of water is vital to domestic water supplies since it is related to public health and water treatment process. This paper presents an investigation on an optical tomography system to estimate the turbidity level in a sample of water. The optical sensors consist of infrared light-emitting diodes (LED) as transmitters and photodiodes as the receivers where the projections of the sensors are designed in fan beam mode. The system was tested using a vertical flow pipe. The Independent Component Analysis (ICA) method was used to display the concentration profile. Results obtained proved that the technique can provide the concentration profile representing the turbidity level of water.